Sustainability Strategy and Competitive Advantage : Case Study from the Construction Industry - Vilhomaa, Iris (2021)
Lately, it has become more and more common for companies to be involved in finding solutions and implementing practices to concerning global public goods, such as pollution and climate change (Kaul et al. 1999, 2003). As stated by Baumann-Pauly & Scherer (2013), the concern is no longer that corporations ought to be participating in addressing these issues, but how companies do it successfully. Hence, one of the main goals of this thesis is to study sustainability strategies of the selected companies in order to uncover how and whether implementing sustainability practices can generate sustained competitive advantage for these companies. This thesis especially targets the construction industry, featuring companies that operate mainly in the Nordics. Construction industry is already addressing global public goods issues such as climate change and sustainability with certificates and licenses, however the construction industry is a major contributor to climate change, air pollution and land waste etc. For the sake of attacking climate change and other harmful factors to our globe caused by construction, it is vital to study the benefits of sustainable business strategy in order to help increase and advocate for sustainable and green building. Ultimately, the results of this qualitative research that combines data from interviews as well as annual reports and other publicly found information could possibly encourage companies to further develop and implement environmentally friendly ways of operating to ensure a better future for our globe.